An Introduction to Immune System with Special Focus on Vaccines for SARS-CoV-2: Part II - Shimray, Chong; Shirol, Shrishail E (SCHOOL SCIENCE, 2021)
This is the second part of the two-part article. It will deal with vaccines, vaccine design and types of vaccines, trials during the development of a vaccine, and the process of approval by concerned authority for public use. It will also discuss on the various strategies used in vaccines against SARS-CoV-2 that cause COVID-19 by taking some examples of the recently approved vaccines